After the siren: the community benefits of Indigenous participation in Australian Rules Football - Dockery, Alfred Michael; Gorman, Sean (Bankwest Curtin Economics Centre, 2017)
Documents the individual and community benefits associated with Indigenous Australians' participation in Australian Rules Football and in organised sport more generally.